Otázka věrohodnosti příčin úmrtí na základě komparace historickodemografických a antropologických metod - Jan Cvrček; Šárka Nekvapil Jirásková (Demografie)
Determining the causes of death in the past on the basis of historical-demographic research encounters the problem of the credibility of extant sources. However, interdisciplinary collaboration between historical demographers and physical anthropologists presents a unique opportunity to verify their informative value. The aim of this study is to verify to what extent the cause of death stated in historical written records corresponds with the finding on the skeleton. The studied sample consists of skeletal remains of 97individuals from Bohemia, Czech Republic, died between 1842 and 2006 from the genealogically documented collection of the Department of Anthropology in the National Museum in Prague. The results showed a significant disproportion between the information recorded in vital records and the results of anthropological analysis. These were mainly unrecognized ethnic diseases that left clear marks on the skeleton as a result of osteolytic metastases. The disparities found illustrate the need for interdisciplinary cooperation in researching past mortality.